Passive UHF RFID tag design for mounting on cylindrical metallic surfaces - Carlos David Morales Peña (2018)
This research proposes an Ultra High Frequency (UHF) exible passive tag antenna for Radio Frequency Identication (RFID) which operates at 902-928 MHz band frequency. The small antenna has a dimension of 13 mm x 28 mm x 0.4 mm and contains a exible commercial substrate with ease of obtaining, for being attached over at and cylindrical metallic surfaces with dierent sizes. The geometry of the tag antenna was optimized, using a genetic algorithm, maximizing its read range at 915 MHz. The antenna performance was evaluated on at and curved surfaces, by simulations of input impedance, gain, reection coecient and read range. Also, measurements of reection coecient of the tag antenna were developed. The results of the RFID tag prove that the designed antenna can be wrapped on cylindrical metallic surfaces with read ranges above one meter, useful for applications of industrial asset management, access control, construction and medical equipment, and identication of small metallic items such as hardware tools, kitchenware, tin cans, and spray bottles. Additionally, in this work, a study about the electromagnetic behavior of the tag antenna mounted on cylinders fabricated with polyethylene terephthalate (PET) materials was developed. Based on optimization process, whose goal is maximizing the coverage ratio of the tag antenna, a read range of about one meter is obtained. Results show that the antenna has a reliable and useful behavior over cylinders with small radius. Furthermore, the addition of a liquid component inside the PET volume, depending on its permittivity, can increase the read range of the tag antenna.